Population structure and natural diet of Astyanax cf. paranae Eigenmann 1914 a typical species of neotropical headwaters streams - Matheus Souza Costa; Welber Senteio Smith (Acta Scientiarum. Biological Sciences, 2019)
This work describes the habits of individuals of the species Astyanax cf. paranae that inhabit Ribeirão do Ferro, a bedside stream. Overall, 92 specimens were analyzed (53 females and 39 males), and the size ranged from class 4.7-5.7 cm to class 10.7-11.7 cm. The females consisted in the larger portion gacor5000 of the samples, except for classes of 4.7-5.7 and 5.7-6.7 cm. The condition factor between males and females (t = 2.1545; p < 0.05) shows distinguished values, with females having higher averages. Fragments of allochthonous insects and plant matter make up the basis of the species' diet. The study showed that the population of A. cf. paranae is predominantly females and have the highest standard for length and weight, which may favor biological diversity and increased larvae and juveniles, maximizing the chance of individuals reaching adulthood. The species prefers an environment with predominance of rocks and logs, which favors shelters. Its diet comes mostly from the riparian forest, with a high dependence on the allochthonous items, thus, these vegetations are very important for maintaining populations of the species.